2020
DOI: 10.3390/jcm9041022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucose Improvement on Nocturnal Sleep Breathing Parameters in Patients with Type 2 Diabetes: The Candy Dreams Study

Abstract: Type 2 diabetes exerts a negative impact on sleep breathing. It is unknown whether a long-term improvement in glycemic control ameliorates this effect. We conducted an interventional study with 35 patients with type 2 diabetes and obstructive sleep apnea (OSA) to explore this. At home, sleep breathing parameters were assessed at baseline and after a 4-month period in which antidiabetic therapy was intensified. Patients who decreased their body mass index ≥2kg/m 2 were excluded. Those with an HbA1c reduction ≥0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Studies in animal models have shown that leptin is a powerful stimulant of ventilation that can prevent respiratory depression in obese animals. There is accumulating evidence that leptin affects the contraction of the upper airway during sleep ( 66 ), suggesting that elevated leptin levels in the central nervous system may prevent the occurrence of OSAS. The increase in serum leptin levels in patients with OSAS may be a compensatory protective mechanism to prevent respiratory depression ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models have shown that leptin is a powerful stimulant of ventilation that can prevent respiratory depression in obese animals. There is accumulating evidence that leptin affects the contraction of the upper airway during sleep ( 66 ), suggesting that elevated leptin levels in the central nervous system may prevent the occurrence of OSAS. The increase in serum leptin levels in patients with OSAS may be a compensatory protective mechanism to prevent respiratory depression ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Better results were obtained in patients treated by insulin alone. These interesting data need to be confirmed in further studies 71 …”
Section: Impact Of Treatmentmentioning
confidence: 87%
“…Only one study has, so far, focused on weight loss intervention in subjects with both prediabetes and obstructive sleep apnea, showing that changes in SpO 2 were associated with changes in insulin sensitivity but not with weight loss [ 33 ]. Similarly, our group has demonstrated that in type 2 diabetes the improvement of metabolic control achieves a significant reduction in sleep breathing parameters not related with weigh modifications [ 6 ]. These results point out a direction for the further improvement of metabolic control in individuals with prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The Sweet Sleep study characterized obstructive sleep apnea (OSA) in patients with type 2 diabetes, providing evidence that the composition of their apnea–hypopnea index (AHI) is characterized by an increase in apnea events, with no differences or even reduction in hypopnea episodes [ 2 ]. Additionally, a small interventional study with 35 patients with type 2 diabetes and OSA has recently shown how the improvement of glycemic control without significant weight loss exerts beneficial effects on sleep breathing parameters [ 6 ]. This multifaceted relationship between diabetes milieu and sleep breathing is based on several pathophysiological mechanisms that include insulin resistance, inflammatory and oxidative stress-activated signaling pathways, leptin resistance and abnormalities in the autonomic nervous system [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%